Quantitative ubiquitylome analysis and crosstalk with proteome/ acetylome analysis identified novel pathways and targets of perifosine treatment in neuroblastoma - Jiang, Min; Hua, Zhongyan; Dong, Yudi; Liu, Zhihui; Thiele, Carol J.; Li, Zhijie (Translational Cancer Research, 2018)
Background: Perifosine, is a third generation alkylphospholipid analog which has promising anti-tumor efficacy in clinical trials of refractory/recurrent neuroblastoma (NB). However, perifosine’s mechanism of action remains unclear. Previously, we have shown that perifosine changes global proteome and acetylome profiles in NB. Methods: To obtain a more comprehensive understanding of the perifosine mechanism, we performed a quantitative assessment of the lysine ubiquitylome in SK-N-AS NB cells using SILAC labeling, affinity enrichment and high-resolution liquid chromatography combined with mass spectrometry analysis. To analyse the data of ubiquitylome, we performed enrichment analysis with gene ontology (GO), the Encyclopedia of Genes and Genomes (KEGG) pathway, ubiquitylated lysine motif, protein complex and protein domain. Protein-protein interaction was conducted to explore the crosstalk between ubiquitylome and previous global proteome/acetylome. Co-immunoprecipitation and western blotting were used to validate the results of the ubiquitylome analysis. Results: Altogether, 3,935 sites and 1,658 proteins were quantified. These quantified ubiquitylated proteins participated in various cellular processes such as binding, catalytic activity, biological regulation, metabolic process and signaling pathways involving non-homologous end-joining, steroid biosynthesis and Ras signaling pathway. Ubiquitylome and proteome presented negative connection. We identified 607 sites which were modified with both ubiquitination and acetylation. We selected 14 proteins carrying differentially quantified lysine ubiquitination and acetylation sites at the threshold of 1.5 folds as potential targets. These proteins were enriched in activities associated with ribosome, cell cycle and metabolism. Conclusions: Our study extends our understanding of the spectrum of novel targets that are differentially ubiquitinated after perifosine treatment of NB tumor cells.